Transport of D-glucose by membrane vesicles from normal and avian sarcoma virus-transformed chicken embryo fibroblasts. - Decker, S (1981)
Transport of D-glucose was examined in membrane vesicles from normal and avian sarcoma virus (ASV)-transformed chicken embryo fibroblasts. The initial rates of D-glucose transport were found to be 3- to 5-fold higher for vesicles from glucose-starved normal cells and ASV-transformed cells when compared with transport rates for vesicles from normal cells and serum-starved normal cells. Cytochalasin B, phloretin, and diethylstilbestrol inhibited the initial rate of transport in all types of vesicles, and 2-deoxyglucose, 3-O-methylglucose, and galactose were competitive inhibitors. At D-glucose concentrations between 0.25 and 5 mM, vesicles from normal and ASV-transformed cells displayed saturation kinetics with a Km value of 5 mM for both types of vesicles, with transformed cell vesicles showing a 3-fold increase in Vmax compared with normal cell vesicles. At D-glucose concentrations between 5 and 25 mM the initial rate of D-glucose transport was proportional to D-glucose concentration. The vesicles also showed an inhibitor-sensitive efflux at rates similar to those observed for influx.